1976
DOI: 10.1159/000458837
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Mechanism of the Changes in Serum and Liver γ-Glutamyl Transpeptidase Activity. II. Experimental Hexachlorobenzene Porphyria in Rabbits

Abstract: The mechanism responsible for the changes in serum and liver γ-glutamyl transpeptidase (γ-GT) activity was studied in a model of experimental hexachlorobenzene porphyria in rabbits. Porphyria followed the administration of hexachlorobenzene in doses of 280 μmol • kg^-1 body weight, which were given daily through a gastric tube over a 20-day period. Serum γ-GT activity and the activities of the lysosomal enzymes β-N-acetylglucosaminidase and α-mannosidase were increased, whereas L-aspartate: 2-oxoglutarate amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1976
1976
2011
2011

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Pietschmann and Raab (27) and Simon et al (11) also found an elevation of SGPT, and Ivanov (28) found an increase in y-glutamyltranspeptidase (y-GT) in rats made porphyric with HCB. However, their experiments do not reveal whether the observed liver damage began before or after the onset of porphyria (i.e., hepatic porphyrin accumulation).…”
Section: Mitochondrial Enzymesmentioning
confidence: 96%
“…Pietschmann and Raab (27) and Simon et al (11) also found an elevation of SGPT, and Ivanov (28) found an increase in y-glutamyltranspeptidase (y-GT) in rats made porphyric with HCB. However, their experiments do not reveal whether the observed liver damage began before or after the onset of porphyria (i.e., hepatic porphyrin accumulation).…”
Section: Mitochondrial Enzymesmentioning
confidence: 96%
“…1 (1,26) (Tables 9 and 10). Pietschmann and Raab (27) and Simon et al (11) also found an elevation of SGPT, and Ivanov (28) found an increase in y-glutamyltranspeptidase (y-GT) in rats made porphyric with HCB. However, their experiments do not reveal whether the observed liver damage began before or after the onset of porphyria (i.e., hepatic porphyrin accumulation).…”
Section: Reactive Intermediatementioning
confidence: 96%
“…However, it is also found in the hepatocyte, in both the cytosol (19) and the smooth endoplasmic reticulum (ER) (where it is susceptible to induction, e.g., through drugs) (20), as well as in mitochondria (21) in the following respective percentages: 15, 75 and 15.…”
Section: Anatomo-cytological Localization Of Ggtmentioning
confidence: 99%